Eosinophils in transbronchial biopsies: a predictor of chronic lung allograft dysfunction and reduced survival after lung transplantation — a retrospective single‐center cohort study. (16th November 2020) - Darley, David R.; Ma, Jin; Huszti, Ella; Fiset, Pierre; Levy, Liran; Hwang, David M.; Pal, Prodipto; Klement, William; Zamel, Ricardo; Keshavjee, Shaf; Tomlinson, George; Singer, Lianne G.; et al.
Abstract: Long‐term outcomes after lung transplantation remain inferior to those of other solid organ groups. The significance of eosinophils detected on transbronchial biopsies (TBBx) after lung transplantation and their relationship to long‐term outcomes remain unknown. A retrospective single‐center cohort study was performed of patients transplanted between January 01, 2001, and July 31, 2018, who had at least 1 TBBx with evaluable parenchymal tissue. Multivariable Cox proportional hazard models were used to assess the associations between eosinophil detection and: all‐cause mortality and Chronic Lung Allograft Dysfunction (CLAD). 8887 TBBx reports from 1440 patients were reviewed for the mention of eosinophils in the pathology report. 112 (7.8%) patients were identified with eosinophils on at least one TBBx. The median (95% CI) survival time for all patients was 8.28 (7.32–9.31) years. Multivariable analysis, adjusted for clinical variables known to affect post‐transplant outcomes, showed that the detection of eosinophils was independently associated with an increased risk of death (HR 1.51, 95% CI 1.24–1.85, p < 0.01) and CLAD (HR 1.35, 95% CI 1.07–1.70, P = 0.01). Eosinophils detected in TBBx are associated with an increased risk of CLAD and death. There may be benefit in specifically reporting the presence of eosinophils in TBBx reports and incorporating their presence in clinical decision‐making.